The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1111/1467-8624.00400
|View full text |Cite
|
Sign up to set email alerts
|

Group Identification in Early Adolescence: Its Relation with Peer Adjustment and Its Moderator Effect on Peer Influence

Abstract: This study was conducted to test whether group identification (importance of the group to the individual) covaried with individual-group similarity on problem behavior; and whether group identification moderated peer group influence on the individual's development of delinquent behavior across a 1-year period. The level of reciprocated nominations within the individual's self-nominated group was controlled for in all analyses. Participants were 190 sixth and seventh graders (during the first year of the study)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
113
2
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 53 publications
5
113
2
9
Order By: Relevance
“…Gilligan (1982) stated that adolescents, particularly females, are more likely to focus on their relationships at school because this is their main context. It is also proposed that girls give more importance to group membership and need more nurturing behavior from their friends than do boys (Newman et al, 2007;Kiesner et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gilligan (1982) stated that adolescents, particularly females, are more likely to focus on their relationships at school because this is their main context. It is also proposed that girls give more importance to group membership and need more nurturing behavior from their friends than do boys (Newman et al, 2007;Kiesner et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Given that a sense of belonging is important for adolescent wellbeing, research has shown that adolescent girls give more importance to group membership, as well as relatedness and connectedness to others, while competition and autonomy are more important for boys (Newman, Newman, Griffen, O'Connor, & Spas, 2007;Sanchez et al, 2005). Also, adolescent girls have more friends than do their male peers, and need more nurturing behavior from their friends than boys do (Kiesner, Cadinu, Poulin, & Bucci, 2002). In addition, Tosolt (2010) expressed that although both girls and boys value teacher care, girls ascribe more importance to academically nurturing behavior, while boys focus on interpersonal caring behavior.…”
mentioning
confidence: 99%
“…Although studies on CSI among females are missing, prior research suggested that women are more likely to form stronger bonds and identification with in-group members because of the greater need to be an accepted and supported member of a group (e.g., Brown et al, 1986;Brown & Lohr, 1987;Kiesner et al, 2002;Newman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…20 Individuals who are similar tend to form groups with greater cohesion, and being recognized as a member seems to increase the sense of identification with the group. 40 Thus, this relationship appears to be bidirectional, because individuals tend to be grouped by their common characteristics and perceive themselves as being more similar when they feel like part of a group. Adolescents may choose a particular sports activity because they share a number of similar characteristics or styles with other players, even in terms of substance use preferences and patterns.…”
Section: Discussionmentioning
confidence: 99%